Technological Advancements Shaping Future Learning Environments - Riveira, Carlose; Fadhila, Amina; O’Reilly, Johanes; Sung, Lin Wei; Kovialenko, Helena (Journal of Studies in Academic, Humanities, Research, and Innovation, 2024)
Technological advancements have brought about significant changes in the world of education, creating a more dynamic and adaptive learning environment. Technologies such as Artificial Intelligence (AI), Augmented Reality (AR), Virtual Reality (VR), the Internet of Things (IoT), and digital learning play a crucial role in shaping the future of education. This study aims to analyze how these technological advancements impact the learning environment and the role of teachers in the future. The method used in this research is a literature review, collecting and analyzing various publications related to the implementation of technology in education. The findings indicate that AI enables personalized learning, AR and VR create immersive experiences, IoT enhances student interaction with the learning environment, and digital learning offers greater flexibility. Despite their potential, the main challenges in implementing these technologies include the need for adequate infrastructure, the digital divide, and the importance of technological literacy among teachers and students. This study concludes that, although technology will transform the role of teachers, they remain a key element in supporting effective learning through the wise and inclusive use of technology